Integrated analysis of the potential, electric field, temperature, pH and tissue damage generated by different electrode arrays in a tumor under electrochemical treatment - Soba, Alejandro; Suárez, Cecilia Ana; Morales González, Maraelys; Bergues Cabrales, Luis Enrique; Bergues Pupo, Ana Elisa; Reyes, Juan Bory; Martínez Tassé, José Pablo (Elsevier Science, 2017)
Fil: Soba, Alejandro. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina